Letter : Patent Leather Shoes for Basque Children - Newman, A. E.
1938-10-19 038-0116-002 REGISTERED OFFICE : BALLOON ST. MANCHESTER, 4 TELEGRAPHIC ADDRESS: "WHOLESALE," E.D.O. LONDON TELEPHONE ROYAL 7221 EXTENSION NO 254. PLEASE ADDRESS YOUR REPLY CO-OPERATIVE WHOLESALE SOCIETY LIMITED, BRANCH ADMINISTRATIVE OFFICE, 99, LEMAN STREET, LONDON, E.1. Our reference A/AEN/HMM. Your reference HVT/FC/EK/138. 19th November, 1938. Dear Mr. Tewson, Patent Leather Shoes for Basque Children. We are in receipt of your letter of the 18th instant, enclosing 18 cut-outs of the shape of the feet of the girls for whom you are requiring first quality patent leather ankle strap shoes, which is having attention. We are arranging for same to be sent to the Basque Children's Home at Arkley, Near Barnet, and for the cost to be debited against the C.W.S. grant of £250. Yours faithfully, pro Society, A.E. Newman Mr. H. V. Tewson, Trades Union Congress, Transport House, Smith Square, London, S.W.1. 292/946/38/117(I)